Revision of the genera Xanthogaleruca Laboissière, 1932 and Pyrrhalta Joannis, 1865 (Coleoptera, Chrysomelidae, Galerucinae) of Taiwan, with type designation of Galerucella lineatipes Takei - Lee, Chi-Feng; Bezděk, Jan (ZooKeys, 2021)
The taxonomic status of Pyrrhalta Joannis, 1865 and allied genera Tricholochmaea Laboissière, 1932 and Xanthogaleruca Laboissière, 1934 is discussed based on the study of Taiwanese species. Tentatively, Xanthogaleruca and Pyrrhalta are regarded as valid genera while Tricholochmaea is a synonym of Pyrrhalta. Fourteen species are recognized and redescribed, including P. gressitti Kimoto, 1969; P. taiwana Kimoto, 1969; P. viridipennis Kimoto, 1981; P. igai Kimoto, 1981; P. meifena Kimoto, 1976; P. maculata Gressitt & Kimoto, 1963; P. tsoui Bezděk & Lee, 2019; P. semifulva (Jacoby, 1885); P. discalis Gressitt & Kimoto, 1963; P. ishiharai Kimoto, 1994; P. shirozui Kimoto, 1969; P. kobayashii Kimoto, 1974; P. ohbayashii Kimoto, 1984; and P. takizawai Kimoto, 1996. Taiwanese populations identified as Xanthogaleruca aenescens (Fairmaire) were misidentified and those are described as a new species, X. yuae sp. nov. Xanthogaleruca aenescens is redescribed for comparison. Eight additional new species of Pyrrhalta are described: P. alishanensis sp. nov., P. houjayi sp. nov., P. formosanensis sp. nov., P. jungchani sp. nov., P. lui sp. nov., P. meihuai sp. nov., P. tahsiangi sp. nov., and P. wulaiensis sp. nov. Type specimens of Galerucella lineatipes Takei, 1916 were rediscovered and are designated as lectotype and paralectotype. Galerucella lineatipes is removed from synonymy with G. calmariensis (Linnaeus, 1767) and regarded as a senior synonym of P. humeralis (Chen, 1942), syn. nov. Most Pyrrhalta species can be classified into four species groups based on their morphological and genitalic similarity. host plants and other biological information are provided for almost all species.
Keywords: Tricholochmaea; leaf beetles; new species; host plant; nomenclature; new synonym; taxonomy